A theoretical framework for psychiatric rehabilitation - L.R. Uys (AOSIS, 1991)
A Theoretical framework for psychiatric rehabilitation is presented. It is based on four existing models in the field and describes the process of relapse, intervening variables, interventions and outcomes. Some interactions between the elements of the framework are given and the research support and implications for nursing are readdressed briefly.